Human cytochrome-P450 enzymes metabolize N-(2-methoxyphenyl)hydroxylamine, a metabolite of the carcinogens o-anisidine and o-nitroanisole, thereby dictating its genotoxicity - Naiman, Karel; Martínková, Markéta; Schmeiser, Heinz; Frei, Eva; Stiborová, Marie (Mutation research. Genetic toxicology and environmental mutagenesis, 2011)
N-(2-Methoxyphenyl)hydroxylamine is a component in the human metabolism of two industrial and environmental pollutants and bladder carcinogens, viz. 2-methoxyaniline (o-anisidine) and 2-methoxynitrobenzene (o-nitroanisole), and it is responsible for their genotoxicity. Besides its capability to form three deoxyguanosine adducts in DNA, N-(2-methoxyphenyl)-hydroxylamine is also further metabolized by hepatic microsomal enzymes. To investigate its metabolism by human hepatic microsomes and to identify the major microsomal enzymes involved in this process are the aims of this study. N-(2-Methoxyphenyl)hydroxylamine is metabolized by human hepatic microsomes predominantly to o-anisidine, one of the parent carcinogens from which N-(2-methoxyphenyl)hydroxylamine is formed, while o-aminophenol and two N-(2-methoxyphenyl)hydroxylamine metabolites, whose exact structures have not been identified as yet, are minor products. Selective inhibitors of microsomal CYPs, NADPH:CYP reductase and NADH:cytochrome-b5 reductase were used to characterize human liver microsomal enzymes reducing N-(2-methoxyphenyl)hydroxylamine to o-anisidine. Based on these studies, we attribute the main activity for this metabolic step in human liver to CYP3A4, 2E1 and 2C (more than 90%). The enzymes CYP2D6 and 2A6 also partake in this N-(2-methoxyphenyl)hydroxylamine metabolism in human liver, but only to ∼6%. Among the human recombinant CYP enzymes tested in this study, human CYP2E1, followed by CYP3A4, 1A2, 2B6 and 2D6, were the most efficient enzymes metabolizing N-(2-methoxyphenyl)hydroxylamine to o-anisidine. The results found in this study indicate that genotoxicity of N-(2-methoxyphenyl)hydroxylamine is dictated by its spontaneous decomposition to nitrenium/carbenium ions generating DNA adducts, and by its susceptibility to metabolism by CYP enzymes.